2003
DOI: 10.1038/ng1179
|View full text |Cite
|
Sign up to set email alerts
|

AAV serotype 2 vectors preferentially integrate into active genes in mice

Abstract: Recombinant adeno-associated virus serotype 2 (rAAV2) is a promising vector for gene therapy because it can achieve long-term stable transgene expression in animals and human subjects after direct administration of vectors into various target tissues. In the liver, although stable transgene expression primarily results from extrachromosomal vector genomes, a series of experiments has shown that vector genomes integrate into host chromosomes in hepatocytes at a low frequency. Despite the low integration efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
252
6
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(267 citation statements)
references
References 29 publications
7
252
6
2
Order By: Relevance
“…Hence, comparing with other viral vectors, rAAV vectors appear to be safer and more efficient, and the existence of different AAV serotypes expands the usefulness of the rAAV vectors, and leads to more specific and strong transgene expression with capsid pseudotypes from alternative serotypes in different organs and tissues [38]. These high promises are somewhat flawed by a recent report indicating that rAAV (type 2) vectors, despite low integration efficiency, may integrate in murine hepatocytes, i.e., quiescent cells, preferentially into actively transcribed genes, and cause small genomic deletions, hence having the potential for dangerous side effects [39,40].…”
Section: Recombinant Adeno-associated Virus Vectormentioning
confidence: 99%
“…Hence, comparing with other viral vectors, rAAV vectors appear to be safer and more efficient, and the existence of different AAV serotypes expands the usefulness of the rAAV vectors, and leads to more specific and strong transgene expression with capsid pseudotypes from alternative serotypes in different organs and tissues [38]. These high promises are somewhat flawed by a recent report indicating that rAAV (type 2) vectors, despite low integration efficiency, may integrate in murine hepatocytes, i.e., quiescent cells, preferentially into actively transcribed genes, and cause small genomic deletions, hence having the potential for dangerous side effects [39,40].…”
Section: Recombinant Adeno-associated Virus Vectormentioning
confidence: 99%
“…rAAV integration studies in the mouse liver reported that a high frequency (53-72%) of integration events occurred in transcribed regions. 9,10 A number of integration hot-spots in the mouse genome was identified, the most prominent being rRNA gene repeats. Those studies also identified integrations (3.5%) near or within cancer-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular concern is the theoretical risk of insertional oncogenesis, as the recombinant form of the virus mediates random incorporation of transgenes into the host chromosomes. 20 Also, the usefulness of AAV as a vector is limited by the relatively small amount of passenger DNA that can be incorporated. Although genes up to 6.0 kb have been packaged into AAV, these oversized viruses were not infectious, 21 and the usual packaging limit for AAV appears to be 5.1-5.3 kb.…”
Section: Vectors For Optic Nerve Gene Therapymentioning
confidence: 99%